"Because we missed the way that we eat at the middle of the day:" Dietary acculturation and food routines among Dominican women. (1st December 2015) - Weisberg-Shapiro, Pamela; Devine, Carol M.
Abstract: Better understanding of dietary change mechanisms among growing immigrant populations is needed in light of increased risk for diet-related chronic health conditions and inconsistent associations between acculturation and diet. This grounded theory research aimed to understand the lived experiences of interactions between food culture and social, economic, and physical environments in an immigrating population, Dominican women living in the Dominican Republic and New York City. Twenty-nine Dominican women participated in qualitative interviews about food and eating behaviors, life course experiences, and environments. Daily food and eating routines, framed by shopping for, preparation of, and consumption of 'la comida' or the main meal, emerged as dominant themes reflecting differences in women's economic, social, and physical environments. Routines were shaped by employment, household characteristics, and the food environment. Participating women attributed weight gain to changes in their food routines following immigration. The construction, disruption, and reconstruction of food and eating routines in response to differing economic, social, and physical environments in the sending and the receiving cultures provided new insights into the relationship between structural and cultural contexts of food and eating in an immigrant population. A food routines framework provides new insights into behavioral and weight changes with immigration. Highlights: Food routines reflected differences in economic, social, and physical environments. Women attributed weight gain after immigration to changes in their food routines. Temporal routines elucidated behavioral and weight changes among immigrants. Changes in food routines were a central process of dietary acculturation.